Educational Quality Assurance Management In Improving And Developing The Middle School Professionalism Teachers - Deny Setiawan (Program Studi Manajemen Pendidikan Islam Institut Agama Islam Sunan Kalijogo Malang, 2021)
This article discusses the management of educator quality assurance in improving and developing teacher professionalism conceptually which includes the implementation of recruitment, the development of teacher professions and termination of employment as an important function in ensuring quality education quality. This article is made by reviewing and gathering information from various references to books, articles and journals that are used as material in conceptually studying and adding insight related to educator quality assurance. The management of educator quality assurance is a good step to support the improvement and acceleration of the improvement of the quality of human resources in the field of education in accordance with the need to improve educator standards and quality, but in implementing educator quality assurance management is expected to be balanced between recruitment, professional development, welfare development and termination of employment. There is still a lot of implementation in the field that causes workload and professional development for senior educators, mediators and juniors and creates new problems in education.